James, Harold. Seven Crashes: The Economic Crises that Shaped Globalization - Carlson, Mark (Journal of Economic Literature, 2025)
Mark Carlson of Board of Governors of the Federal Reserve System reviews “Seven Crashes: The Economic Crises that Shaped Globalization” by Harold James. The Econlit abstract of this book begins: “Explores the transformative effect of supply crises on globalization, promoting the argument that new institutions arise out of responses to these disruptions and that this changes the way that people conceive of the economic process.”